The Analysis Of Multi Representation Ability Of Students On Elasticity Theory And Hooke Laws - Suharsono, Devina Laraswati; Wasis, Wasis; Zainuddin, Abu (Jurnal Penelitian Pendidikan Fisika, 2021)
The ability of students to interpret a physics concept can be known by using a multi-representation test instrument. This research aims to analyze the multi-representation ability of students on elasticity and Hooke's law. This research is a descriptive exploratory study using a multi-representation instrument. The instrument is in the form of an essay with 6 items, the instrument has been validated by 2 physics lecturers at the Universitas NegeriÂ  Surabaya. Research respondents were 23 students of class XI SMA Negeri 3 Blitar as many as 1 class for the 2020/2021 school year Based on the results of the analysis, the research results obtained: a) the research instrument in the form of a valid multi-representation question with the value 0,87 category very valid; b) not all multi-representation abilities were mastered by students. The data showed that the students' lack of multi-representation ability was verbal representation ability with a percentage of 65.21%, while the highest representation ability was mathematical representation and symbols with a percentage of 92.75%.Â